10 Years' Plaque Incision and Vein Grafting for Peyronie's Disease: Does Time Matter?. Issue 1 (1st January 2016) - Wimpissinger, Florian; Parnham, Arie; Gutjahr, Georg; Maksys, Sandra; Baierlein, Martin; Stackl, Walter
ABSTRACT: Introduction: Surgical correction is advocated in patients with stable Peyronie's disease (PD) and severe curvature of the penis. Contemporary series demonstrate favorable outcomes based on relatively short follow-up periods. However, long-term follow-up is rarely reported and there is a paucity of evidence on the influence of patients' age, comorbidities, and natural history on surgical outcomes. Aims: The present study aims to examine the influence of patient's age, comorbidities, severity of the disease, and natural history of PD on long-term outcomes and satisfaction following plaque incision and vein grafting for PD. Methods: Patients with follow-up of more than 10 years who underwent plaque incision and grafting (Lue technique) for stable PD were included in the study. Main Outcome Measures: A combination of prospective and retrospective analysis of patients' histories, anatomical, functional, and surgical parameters, development of PD recurrences, improvements of sexual functions, and overall satisfaction were performed between 1992 and 2014. Multiple logistic regression models were applied to calculate adjusted odds ratios for predictors for development of erectile dysfunction (ED) and PD recurrence. Results: Thirty patients with a median age of 57.5 years were eligible for inclusion in the study with a mean follow-up of 13.0 years (range 10.0–17.6). Angle of preoperative penile deviation was 40° to 110° (median 90°). On follow-up, 26 men (86.7%) had a straight erect penis. Eleven men (36.7%) developed ED, of whom 2 (6.7%) had other comorbidities contributing to their ED. Twenty-five men (83.3%) were still sexually active with or without medication. The mean percentage improvement in sexual function was 69.0%, with 17 men (56.7%) reporting 100% improvement and 7 (23.3%) reporting no improvement. Perceived penile shortening occurred in 13 patients (43.3%) and 6 patients (20.0%) experienced penile hyposensitivity. PD/plaque recurrence was found in 7 men (23.3%). The mean overall satisfaction with the procedure was 73.0%, with 18 men (60.0%) still 100% satisfied and 6 (20.0%) reporting satisfaction below 50%. Conclusion: Improvement of sexual function and overall satisfaction remain high at 10 years follow-up and make the technique a safe and effective form of treatment in carefully selected patients.